Preparation method of reed biomass adsorbent for removing formaldehyde
By preparing reed biomass adsorbents, the problems of low formaldehyde removal efficiency and environmental pollution in the prior art are solved, efficient and environmentally friendly formaldehyde adsorption and removal are achieved, and the use efficiency of adsorbents is improved through recycling.
Patent Information
- Application Number
- CN202411745526.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to effectively remove formaldehyde, and traditional adsorbents are highly polluted to the environment, and biological methods are slow to process and have limited application scope.
By preparing reed biomass adsorbents, including cooking, primary soaking, secondary soaking, rinsing, drying and sieving, an efficient formaldehyde adsorbent is formed and its recycling is achieved through the desorption process.
It realizes efficient adsorption and removal of formaldehyde, reduces environmental pollution, and maintains the adsorption capacity through multiple desorption, demonstrating the recycling and efficiency of the adsorbent.
Smart Images

Figure CN119701867A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorbents, and in particular relates to a method for preparing a reed biomass adsorbent for removing formaldehyde. Background Art
[0002] Formaldehyde is a colorless irritant gas that is irritating to the eyes and nose. It is easily soluble in water and ethanol and is volatile. The concentration of its aqueous solution can be as high as 55%. The well-known formalin is a 35-40% formaldehyde aqueous solution. Formaldehyde has been identified by the World Health Organization as an invisible substance that causes deformities and cancer. Mild excess formaldehyde may cause chronic poisoning. Formaldehyde is a world-recognized carcinogen that is very harmful to the nervous and respiratory systems of the human body. When the formaldehyde concentration exceeds 0.1 mg / m 3 When the concentration exceeds 0.5mg / m 3 There will be strong irritation and tearing when it exceeds 0.6mg / m 3 It can cause breathing difficulties and throat pain, and more than 30 mg / m 3 When people are in a formaldehyde atmosphere for a long time, it can cause gene mutations in human tissues, leukemia, chromosomal abnormalities and other diseases. Pregnant women and children are particularly sensitive to formaldehyde pollution.
[0003] The genus Phragmites is a perennial emergent herb of the Poaceae family. It has strong vegetative reproduction ability, rich genetic diversity and strong phenotypic plasticity. Reed has a strong ability to adapt to the environment, and has the functions of consolidating soil and slope protection, purifying water bodies, inhibiting algal blooms and protecting biodiversity. At present, formaldehyde purification technologies at home and abroad are mainly divided into adsorbents, photocatalysis and biological methods. As a traditional formaldehyde purification method, adsorbents have the advantages of strong adsorption capacity and low cost. The multi-scale simulation of the dynamic adsorption mechanism of formaldehyde by activated carbon studied the dynamic adsorption mechanism of formaldehyde by traditional adsorbent activated carbon; photocatalytic technology uses photocatalysts to decompose formaldehyde under light conditions, which has the characteristics of no pollution and high efficiency. TiO2 modified ACF photocatalytic degradation of formaldehyde has a good effect, especially for the degradation of low-concentration formaldehyde, but the activity and stability of the photocatalyst still need to be improved. The biological method degrades formaldehyde through microorganisms, which has the advantages of environmental protection and safety, but the processing speed is slow and the scope of application is limited. Future research will focus more on the practical application and industrialization of indoor formaldehyde removal technology. With the maturity of technology and the reduction of cost, it is efficient and safe.
[0004] In summary, through in-depth research on the mechanism of action and application potential of reed in purifying formaldehyde, it is expected to provide a green, economical and effective solution for improving indoor air quality and contribute to the realization of sustainable development goals. Summary of the invention
[0005] In view of the above analysis, the present invention proposes a biomass adsorbent and a preparation method thereof which can fully utilize reed waste, has good adsorption effect, and can be recycled for formaldehyde adsorption. The present invention is achieved by the following technical means:
[0006] The present invention first discloses a method for preparing a reed biomass adsorbent for removing formaldehyde, comprising:
[0007] (1) Steaming: Rinse the reeds, steam them in boiling water, and remove them for later use;
[0008] (2) Initial soaking: soak the steamed reeds in KCl solution and remove them for later use;
[0009] (3) Secondary soaking: soak the reeds after the initial soaking in 0.12 mol / L ethyl acetate solution for 17.2 h;
[0010] (4) Rinse: Rinse the soaked reeds with tap water until neutral;
[0011] (5) Drying: Place the washed reeds in a blower box and dry them for later use;
[0012] (6) Screening: Crush the dried reeds, pass through a 40-60 mesh sieve, and package and seal for storage.
[0013] Furthermore, the cooking time in step (1) is 8-15 minutes.
[0014] Furthermore, in step (2), the concentration of the KCl solution is 0.1 mol / L, and the immersion time is 2 h.
[0015] Furthermore, the drying temperature of the blower in step (5) is 60-100°C.
[0016] The invention also discloses a reed biomass adsorbent prepared according to any of the above preparation methods.
[0017] The invention also discloses an application of the reed biomass adsorbent in removing formaldehyde.
[0018] Furthermore, the amount of the reed biomass adsorbent used was 3 g, and the formaldehyde concentration was 1.6 g / m 3 ; The adsorption time is 150 minutes; the adsorption temperature is room temperature 20℃-30℃.
[0019] Furthermore, the application also includes a desorption process:
[0020] The reed biomass adsorbent used for formaldehyde adsorption is placed in the sun for drying and ventilation for several times to complete desorption.
[0021] Furthermore, the several times is 7 times; and the adsorption level of formaldehyde by the reed biomass adsorbent after desorption is greater than 15%.
[0022] The beneficial effects of the present invention are:
[0023] The adsorption effect of the reed biomass adsorbent prepared by the present invention is better than that of other adsorbent materials on the market, and the pollution to the environment is reduced. Characterization and analysis of unmodified reeds, modified reed adsorbents and adsorbed reed adsorbents are performed, and it is analyzed that the microscopic morphology changes before and after adsorption, and the functional groups contained play an adsorption role.
[0024] After being desorbed 7 times, the reed biomass adsorbent prepared by the present invention still has a high adsorption capacity for formaldehyde, and the overall adsorption level is still maintained at more than 15%, and the removal rate of the first 3 times is also maintained at a high level of more than 25%. It proves that the modified reed can be recycled and has a high adsorption effect. It is a pollution-free and harmless biosorbent. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope image; A is the original reed, B is the reed biomass adsorbent prepared by the present invention, and C is the reed after adsorbing formaldehyde.
[0026] Figure 2 The figures are infrared spectra of reeds in different forms; 1 is the untreated original reed, 2 is the reed after formaldehyde adsorption, and 3 is the reed biomass adsorbent prepared by the present invention.
[0027] Figure 3 The present invention provides a horizontal comparison result of the reed biomass adsorbent prepared in the present invention and other materials in formaldehyde adsorption.
[0028] Figure 4 The invention discloses the adsorption effect of the reed biomass adsorbent prepared by the invention on formaldehyde after desorption and regeneration. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0030] Unless otherwise defined, the technical or scientific terms used herein shall have the common meanings understood by persons with ordinary skills in the field to which the present invention belongs. The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, words such as "one" or "a" do not indicate a quantity limitation, but indicate the existence of at least one.
[0031] Example 1
[0032] A method for preparing a reed biomass adsorbent for removing formaldehyde, comprising:
[0033] (1) Steaming: Rinse the reeds and steam them in boiling water for 8-15 minutes. Remove and set aside;
[0034] (2) Initial soaking: Soak the steamed reeds in a 0.1 mol / L KCl solution for 2 h, then remove and set aside;
[0035] (3) Secondary soaking: soak the reeds after the initial soaking in 0.12 mol / L ethyl acetate solution for 17.2 h;
[0036] (4) Rinse: Rinse the soaked reeds with tap water until neutral;
[0037] (5) Drying: Place the washed reeds in a blower at 60-100°C for drying;
[0038] (6) Screening: Crush the dried reeds, pass through a 40-60 mesh sieve, and package and seal for storage.
[0039] Application Example 1
[0040] Determination of formaldehyde adsorbed by reed
[0041] According to the optimal combination scheme, a large amount of reed residue was prepared. When conducting a single factor experiment, the levels of other factors are required to be constant, and the five factors of residue particle size, addition amount, adsorption temperature, pollution source concentration, and time are studied, and adsorption tests are carried out with different gradients.
[0042] a. Particle size of residues: The prepared reed residues were sieved through 18, 40, 60, 80, and 100 mesh sieves, and the experiment was carried out with these five kinds of residues as the particle size gradient: 1g of each of the five kinds of particle size residues was taken, and the formaldehyde concentration in the closed box was uniformly set to 1.85mg / m 3 , adsorption time is 30min, and the removal rates of 5 kinds of residue particle sizes are calculated respectively.
[0043] b. The amount of slag added was selected with a slag particle size of 40-60 mesh for adsorption test: 1-3g of slag was weighed in 5 gradients, and the formaldehyde concentration in the closed box was uniformly set at 1.85mg / m 3 The adsorption time was uniformly set to 30 min, and the removal rates of the five types of residues were calculated respectively.
[0044] c. Adsorption temperature Different indoor temperatures were selected as the adsorption temperature, and the adsorption test was carried out in five gradients: 1g of slag with a particle size of 60 mesh was taken, and the formaldehyde concentration in the closed box was uniformly set to 1.85mg / m 3 The adsorption time was uniformly set to 30 min, and the formaldehyde removal rate at the corresponding adsorption temperature was calculated.
[0045] d. Pollution source concentration The pollution source concentration is selected as 0.8, 1.2, 1.6, 2, 2.4 mg / m 3 , the adsorption experiment was carried out in five gradients: 1g of slag with a particle size of 60 mesh was taken, the adsorption time was uniformly set to 30min, and the removal rates of the five types of slag were calculated respectively.
[0046] e. Adsorption time was divided into 5 gradients for adsorption test: 1g of slag with a particle size of 60 mesh was taken, and the formaldehyde concentration in the closed box was uniformly set to 1.85mg / m 3 The adsorption time was set to 30, 60, 90, 120, and 150 min, respectively, and the formaldehyde removal rates at the corresponding adsorption temperatures were calculated.
[0047] Single factor test results
[0048] Analysis of the effect of particle size on formaldehyde adsorption
[0049] As the slag particle size increases, the removal rate first increases and then decreases, reaching the minimum at 100 mesh and reaching a peak at 60 mesh (F=59.152 and P<0.01). When the slag particle size is 60 mesh, the adsorption performance is the best, so the subsequent experiments were carried out using 60 mesh.
[0050] Analysis of the effect of addition amount on formaldehyde adsorption
[0051] At first, the removal rate increased with the increase of the amount of residue added. When the residue was added to a certain mass of 2.5g, the growth trend of the removal rate was smooth (F=241.499 and P<0.01). The modified reed with 3g added had the highest formaldehyde adsorption performance, followed by the modified reed with 2.5g added, and the modified reed with 1g added had the lowest adsorption performance.
[0052] Analysis of the effect of adsorption temperature on formaldehyde adsorption
[0053] The adsorption effect of reed on formaldehyde first increased and then decreased with the increase of temperature. The removal rate would decrease when the temperature was lower or higher than 24℃ (F=26.74 and P<0.01). Within the experimental range, the adsorption effect on formaldehyde was the best when the adsorption temperature was 24℃. Due to the uncontrollability of actual environmental factors, subsequent experiments were carried out at random room temperature.
[0054] Analysis of the effect of pollutant concentration on formaldehyde adsorption
[0055] The adsorption effect of reed on formaldehyde first increased and then decreased with the increase of pollutant concentration. The pollutant concentration was 1.6 mg / m 3 When the removal rate reaches the peak value, the adsorption effect is the best, which is lower or higher than 1.6 mg / m 3 The removal rate will be reduced (F = 79.254 and P < 0.01), and the pollutant concentration is 1.6 mg / m 3 The most significant result was when the pollutant concentration was 1.6 mg / m 3 The adsorption capacity is the strongest.
[0056] Analysis of adsorption time on formaldehyde adsorption effect
[0057] The adsorption effect of reed on formaldehyde increases with the increase of adsorption time. When the adsorption time is 150 minutes, the removal rate reaches a peak value (F=277.792 and P<0.01), and the adsorption effect is the best.
[0058] In summary, the present invention selects 3g of reed biomass adsorbent to have a concentration of 1.6g / m 3 The formaldehyde adsorption time was 150 minutes and the adsorption temperature was 24℃, which was the best.
[0059] Test Example 2
[0060] Characterization and observation of reed adsorption materials
[0061] a. SEM observation
[0062] In this experiment, the main focus was on observing the differences in characterization between the original reed residue and the modified reed residue before and after adsorption, and analyzing the differences from the fiber network structure.
[0063] b. FTIR analysis
[0064] FTIR (Fourier Transform Infrared Spectrometer) produces infrared spectra of samples and infers their molecular structure. The formaldehyde adsorption mechanism is analyzed and the optimal modified reed adsorption type is inferred.
[0065] c. Element Analyzer
[0066] The main analysis was conducted on the changes in elements such as C, N, H, and S after treatment and adsorption of the three raw materials: untreated reed residue, treated reed residue, and adsorbed reed residue, and the modification effect of the modification treatment on the material was accurately analyzed.
[0067] d.BET parameter analysis
[0068] BET (specific surface area) refers to the total surface area occupied by 1g of solid. Generally, the larger the specific surface area, the stronger the adsorption capacity. BET data is used to analyze the physical structure of modified reed adsorption.
[0069] Depend on Figure 1 It can be seen that the information provided by the microscopic morphological images obtained by scanning electron microscopy can intuitively observe the changes in reeds before and after modification and before and after adsorption. It can be seen that since reeds are composed of a large amount of cellulose, lignin and hemicellulose, their own microscopic morphological structure is loose and porous. The reeds that have been modified but have not adsorbed formaldehyde have obviously more pores than the unmodified reeds, and the overall surface is rougher. This structure can provide more implantation sites for the adsorption process and better adsorption effect. The overall surface of the modified and adsorbed reeds is smoother than that of the unmodified and modified but not adsorbed reeds. This is because the loose microporous structure is filled with the adsorbed substance during the adsorption process.
[0070] exist Figure 2 In the figure, 1 is the original untreated reed, 2 is the optimal modified reed after adsorption, and 3 is the optimal modified reed. -1 , 3437cm -1 , 3419cm -1 There is an obvious absorption peak, which means that the reed material molecules contain a large amount of -OH. The intensity of the absorption peak of the reed after adsorption changes significantly, indicating that the free -OH plays a significant role in the adsorption process. -1 At the same time, at the wave number 1735cm -1 There is C=O stretching. 1050cm -1 It is the CO stretching vibration absorption peak.
[0071] In summary, the above functional groups play different roles in the adsorption reaction process, and hydroxyl plays a decisive role, which proves that this adsorption is a chemical-dominated adsorption process.
[0072] The element results are shown in Table 1:
[0073] Table 1 Element analyzer analysis table
[0074] Material Narea Carea Harea Sarea N% C% H% S% Original reed 555 21246 8898 34 0.756 41.14 5.798 0.1388 Modified reed 250 23157 9324 14 0.322 44.4 5.973 0.058 Adsorption reed 378 22773 9516 21 0.489 43.12 6.001 0.0824
[0075] The following information can be obtained from the changes in the elements in the elemental analysis in Table 1: the C content of the optimized reed increased from 41.14 to 44.4, and the H content increased from 5.798 to 5.973. This is due to the esterification reaction between ethyl acetate and cellulose, which introduced a large number of carboxyl groups and increased the adsorption sites.
[0076] The specific surface area and pore size analysis results are shown in Table 2:
[0077] Table 2 Analysis of specific surface area and pore size of reed
[0078] Test items Modified reed <![CDATA[Specific surface area (m 2 / g)]]> 1.743 <![CDATA[Pore volume (cm 3 / g)]]> 0.005 Pore size distribution (d) 3.533
[0079] According to the results in Table 2, the specific surface area of the modified reed is 1.743 m 2 / g, pore volume is 0.005cm 3 / g and the pore size distribution is 3.533d, so the modified reed has a strong adsorption capacity.
[0080] Test Example 3
[0081] Horizontal comparison test of five adsorbents
[0082] In the same environment, reeds and adsorption materials prepared from them were tested with bamboo charcoal, activated carbon, diatomaceous earth, and resin for adsorption. The specifications are 18 mesh for resin, 60 mesh for activated carbon, 325 mesh for diatomaceous earth, 60 mesh for bamboo charcoal, and 60 mesh for original and modified reeds. 1g of each adsorption material was taken, and the adsorption time gradient was set to 30min, 60min, 90min, 120min, and 150min. Each adsorption material was tested 3 times with different gradients, and its average removal rate was calculated to compare the adsorption effect. For specific results, see Figure 3 .Depend on Figure 3 By comparison, it can be seen that at room temperature of 22°C, different adsorption materials have different effects on formaldehyde purification. The specifications of the adsorption materials are 18 mesh resin, 60 mesh activated carbon, 325 mesh diatomaceous earth, 60 mesh bamboo charcoal, and 60 mesh optimized and original reeds. Different adsorption materials or different times will have a significant impact on the adsorption effect. There is also an interaction between materials and time, which affects the adsorption effect. From the variance analysis table, F 材料 =252.932 and P<0.01, F 时间 =5.901 and P<0.01, F 材料×时间 =365.464 and P < 0.01. Among the six adsorption materials, modified reed has the best adsorption effect, followed by bamboo charcoal.
[0083] Test Example 4
[0084] Experiment on desorption and recycling of modified reed residue
[0085] Desorption is the reverse process of adsorption. After the adsorbent is saturated with adsorption, it can be desorbed by drying it in the sun to restore a certain adsorption capacity. This not only maximizes the utilization rate of reeds, but is also very environmentally friendly and meets the national sustainable development requirements.
[0086] Procedure: Weigh 2.5 g of the best residue at 1.8 mg / cm 3 The formaldehyde adsorption test is carried out in a closed box, and its removal rate is calculated. The residue after adsorption is dried and ventilated in the sun and the above test process is repeated. The test is repeated many times to explore the changes in the adsorption performance.
[0087] For detailed results, see Figure 4 ,according to Figure 4 The results show that after 7 desorption experiments, the overall adsorption level remains above 15%, and the removal rate of the first 3 times also remains at a high level of more than 25% (F = 171.475 and P < 0.01). The modified reed still maintains a high level after multiple adsorptions and is a highly efficient adsorbent that can be recycled.
[0088] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.
[0089] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This description method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A method for preparing a reed biomass adsorbent for removing formaldehyde, comprising: (1) Steaming: Rinse the reeds, steam them in boiling water, and remove them for later use; (2) Initial soaking: soak the steamed reeds in KCl solution and remove them for later use; (3) Secondary soaking: soak the reeds after the initial soaking in 0.12 mol / L ethyl acetate solution for 17.2 h; (4) Rinse: Rinse the soaked reeds with tap water until neutral; (5) Drying: Place the washed reeds in a blower box and dry them for later use; (6) Screening: Crush the dried reeds, pass through a 40-60 mesh sieve, and package and seal for storage.
2. The preparation method according to claim 1, wherein: The cooking time in step (1) is 8-15 minutes.
3. The preparation method according to claim 1, wherein: The concentration of the KCl solution in step (2) is 0.1 mol / L, and the soaking time is 2 h.
4. The preparation method according to claim 1, wherein: The drying temperature of the bellows in step (5) is 60-100°C.
5. A reed biomass adsorbent prepared according to the preparation method according to any one of claims 1 to 4.
6. Use of the reed biomass adsorbent according to claim 5 in removing formaldehyde.
7. The use according to claim 6, wherein: The usage of the reed biomass adsorbent is 3g, and the formaldehyde concentration is 1.6g / m 3 ; The adsorption time is 150 minutes; the adsorption temperature is room temperature 20°C-30°C.
8. The use according to claim 6, further comprising a desorption process: The reed biomass adsorbent used for formaldehyde adsorption is placed in the sun for drying and ventilation for several times to complete desorption.
9. The use according to claim 8, wherein: The said number of times is 7 times; The adsorption level of formaldehyde by the desorbed reed biomass adsorbent is greater than 15%.
Citation Information
Cited By
Cotton stalk derived porous carbon material as well as preparation method and application thereof
CN121849944A